A review of human identification methods used at Salt River Mortuary, South Africa - Mokoena, Motshidisi (Department of Pathology, 2025)
Identification of deceased individuals is important in medico-legal investigations for many reasons. Unfortunately, many bodies remain unidentified in South Africa. The South African legislation provides a guideline for human identification processes to be followed at forensic mortuaries, particularly surrounding the timeframes of various scientific analyses to be completed. However, it is unknown whether this guidance is followed and if timeframes are met, especially considering the high caseloads and low resources in South Africa. Thus, this study aimed to determine how identification procedures at Salt River Mortuary (SRM) are performed and compared the timeline of identification procedures with South African legislative guidance. During 1 January 2020 - 31 December 2020, 3072 individuals had a suspected identity and 410 had an unknown identity upon admission to SRM. Visual recognition was the most used method of identification (n = 2890/3482, 83.0%), and scientific methods of identification (fingerprints (n = 50), DNA (n = 126), and odontology (n = 1)) were successful in identifying a further 4.99% (n = 174/3482) individuals. Unidentified and unclaimed individuals made up 2.96% (n = 103/3482) and 2.01% (n = 70/3482) of the total caseload, respectively – but scientific analyses were not consistently carried out on these cases. Samples for DNA analysis were typically collected during the autopsy (approximately 3-4 days after death), but fingerprint analysis was not requested within the stipulated timeframe of 7 days. The turnaround times for scientific reports usually took longer than 30 days. Only DNA reports from the private laboratory, Unistel, were received timeously, however, resultant DNA profiles were not uploaded to the National Forensic DNA Database, thus diminishing their value for identification. These results show that several aspects of the legislation are not always followed, and efforts to address the shortcomings identified in this study are urgently needed to improve identification outcomes.